Patient safety as a radiotherapy department: how can we enhance safety? - Eiras, Margarida (2009)
Purpose: Medical errors can be classified into five categories: poor decision making, poor communication, inadequate patient monitoring, patient misidentification, inability to respond rapidly, and poor patient tracking. Employing innovative information technologies in correcting these deficiencies is the current trend in enhancing patient safety. Radiofrequency (RF) identification is one technology that has significant potential to secure the medical supply chain and increase the safety and efficiency of healthcare processes. It is our purpose to identify patient waiting times; identify treatment unit occupation and guarantee patient and its accessories’ identification.